EFEKTIVITAS MODEL PEMBELAJARAN PBL BERBANTUAN MIKRO ANIMASI TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII SMP NEGERI 4 PEKALONGAN - Miladiya Tsania; Rini Utami (INSPIRAMATIKA, 2026)
This study aims to explain the effectiveness of PBL learning model assisted by micro animation on students' concept understanding ability at SMP Negeri 4 Pekalongan. This research is a quantitative research with the type of quasi experiment using Posttest Only Control Design. The research sample consisted of 2 classes selected by Cluster random sampling, namely class VIII C as the experimental class and class VIII B as the control class. The data collection method used is using the description test method which is then analyzed using the mean difference test and proportion test. The results showed that the average concept understanding ability of students by applying the PBL learning model assisted by micro animation fully exceeded the KKTP limit and there was a significant average difference between the experimental and control classes. Therefore, the PBL learning model assisted by micro animation is effective on students' concept understanding ability. Keywords: PBL, micro animation, conceptual understanding, mathematics.